Review Article : Peningkatan Literasi Lingkungan Siswa di Sekolah - Ahmadi, Zigi Saka (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2022)
Environmental problems have become a global issue that is currently being widely discussed. Environmental problems that occur are caused by climate change, the extinction of natural resources, to environmental damage caused by human actions. Low public awareness of the environment, one of which is due to the low literacy ability of the community. One of the efforts to improve environmental literacy attitudes is through formal education by implementing learning activities that can improve students' environmental literacy skills. This study aims to find out ways or efforts to improve student environmental literacy in schools through the literature review method, which is a literature search to collect data from various sources, such as: journals, books, internet, and other libraries. Based on the review of articles that have been carried out, there are several efforts that can be made to optimize or improve environmental literacy in schools, including by structuring the curriculum, conducting learning that provides direct experience that is supported by active learning using various varied methods and its implementation can be done inside or outside the school. outside the classroom, using problem-solving-based learning models, implementing adiwiyata program, and using interesting learning media.